PSYCHOLOGICAL FACTORS OF LEADERSHIP TRAINING - Каримжанова Ёкутхон Уринбаевна (Ecominds Press, 2025)
The training of leading specialists in management in higher educational institutions requires psychological knowledge. When updating the content of educational standards and standard curricula for the training of leaders in the field of management, it is necessary to include psychological disciplines. In any field where management processes are properly organized, there will always be growth and development. fair, positive and reasonable in the field of management, is interpreted as one of the topical issues.
Keywords: Biography, leader, manager, standard, standard curriculum, curricula, psychological disciplines, content of education, training for leadership, quality education, entrepreneurship, behavior, motivation.